Surface treatment method for improving dispersity of nano calcium carbonate
By forming a coating layer of calcium phosphate and sodium fatty acid on the nano calcium carbonate, the poor dispersion caused by soft agglomeration of nano calcium carbonate is solved, and its dispersion performance and stability in silicone glue are significantly improved.
Patent Information
- Application Number
- CN202411662999.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The poor macroscopic dispersion of nano calcium carbonate due to soft agglomeration affects its dispersion performance in silicone glue, resulting in poor dispersion of products after storage and extrusion, affecting customer use and causing economic losses.
Calcium phosphate coating layer and sodium fatty acid coating layer are used to form a synergistic coating structure through high and low temperature processes and metathesis method to reduce soft agglomeration and improve the dispersion of nano calcium carbonate in silicone glue.
It significantly improves the dispersion and stability of nano calcium carbonate in silicone glue, slows down soft agglomeration, extends the service life of the product, and reduces economic losses.
Smart Images

Figure BDA0005143924590000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of calcium carbonate preparation, and in particular to a surface treatment method capable of improving the dispersibility of nano calcium carbonate-filled silicone adhesive. Background Art
[0002] Dispersibility has always been the most important point in the research of nano calcium carbonate preparation. A large number of studies have been devoted to improving the dispersibility of nano calcium carbonate, and this dispersibility refers more to microscopic dispersibility, but there are few reports on the macroscopic dispersibility of applied filling.
[0003] Dispersibility can be divided into micro-dispersibility and macro-dispersibility. Micro-dispersibility refers to the dispersion state of a single nano-scale calcium carbonate particle at a microscopic scale. If the nano-calcium carbonate exists independently as a single particle and does not form agglomerates several times larger with other particles due to adsorption and aggregation, it can be considered to have good micro-dispersibility, otherwise it is poor micro-dispersibility. Macro-dispersibility refers to a dispersion index of nano-calcium carbonate filled in the substrate by the application manufacturer at a macroscopic scale. Taking the application of silicone glue as an example, nano-calcium carbonate and silicone resin are first evenly mixed to prepare a base glue, and then the base glue is used to prepare a butterfly sample. Finally, the dispersion is judged by the particle distribution of the base glue on the butterfly sample. If no particles visible to the naked eye are found in the base glue, it can be considered to have good macro-dispersibility, but if there are obvious particles in the base glue (mostly in millimeters in diameter), the more particles there are, the worse the macro-dispersibility is.
[0004] There is a certain correlation between the micro-dispersibility and macro-dispersibility of nano-calcium carbonate. Generally speaking, the better the micro-dispersibility of nano-calcium carbonate, the easier it is for its macro-dispersibility to deteriorate. For macro-dispersibility, there are often two situations, one is poor dispersibility caused by hard agglomeration, and the other is poor dispersibility caused by soft agglomeration. The reason for hard agglomeration is generally that the nano-calcium carbonate has not been fully crushed and deagglomerated, which is a relatively easy problem to solve. However, the phenomenon of poor macro-dispersibility caused by soft agglomeration is very common, which has troubled many nano-calcium carbonate manufacturers and is not easy to solve. For nano-calcium carbonate powders that are prone to soft agglomeration, their macro-dispersibility is generally very good when they are first produced, but after long-term storage and extrusion, their dispersibility will gradually deteriorate, seriously affecting customer use, and even leading to product returns and economic losses.
[0005] According to research, poor macroscopic dispersibility caused by soft agglomeration is related to surface treatment. Generally, the phenomenon of poor macroscopic dispersibility caused by soft agglomeration can be alleviated by increasing the repulsive force between nano-calcium carbonate particles, reducing the use of treatment agents that easily cause adhesion and agglomeration, and adding substances that hinder adhesion and agglomeration. At present, there are almost no reports on related research. It can be seen that it is necessary to develop a surface treatment method that can improve the dispersibility of nano-calcium carbonate-filled silicone adhesive. Summary of the invention
[0006] The purpose of the present invention is to provide a surface treatment method that can improve the poor dispersibility of nano calcium carbonate caused by soft agglomeration. The present invention first coats the nano calcium carbonate with a layer of calcium phosphate, then uses a high and low temperature process to make sodium stearate more evenly coat the nano calcium carbonate, and finally continues to coat calcium stearate by double decomposition. The three coating layers can produce a synergistic effect, which can reduce the soft agglomeration caused by extrusion, and finally improve the dispersibility of nano calcium carbonate filled silicone glue.
[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A surface treatment method for improving the dispersibility of nano calcium carbonate comprises the following steps:
[0009] (1) selecting high-quality limestone and calcining it at high temperature to obtain raw lime, then digesting the raw lime with tap water to obtain lime milk, and then subjecting the lime milk to carbonation reaction with carbon dioxide in a carbonation tower, and obtaining a nano calcium carbonate suspension after the reaction is completed;
[0010] (2) transferring the calcium carbonate suspension of step (1) into a treatment tank with heat preservation and cooling functions, heating the suspension to 85-100° C., then adding a suspension containing 2.0-5.0% calcium hydroxide (calcium carbonate dry basis weight), starting stirring, and then adding a corresponding amount of phosphoric acid solution to the suspension at a regular interval of 10-30 minutes. When the phosphoric acid solution is added, a 1# calcium carbonate suspension can be obtained;
[0011] (3) maintaining the temperature of the 1# calcium carbonate suspension at 85-100° C., adding a solution containing 0.5-1.5% sodium fatty acid (calcium carbonate dry basis weight), and then slowly cooling while stirring for surface treatment, the cooling time being 30-60 min, and when the temperature drops to 30° C., a 2# calcium carbonate suspension can be obtained;
[0012] (4) reheating the 2# calcium carbonate suspension to 65-80° C., adding a solution containing 2.5-3.5% fatty acid sodium (calcium carbonate dry basis weight), starting stirring, and then continuing to add a corresponding amount of soluble calcium salt solution to the suspension at regular intervals of 10-20 min to coat the fatty acid calcium;
[0013] (5) Dehydrating the calcium carbonate slurry through a filter press, drying, and crushing to obtain nano calcium carbonate finished powder.
[0014] Furthermore, the concentration of the phosphoric acid solution in step (2) is 5-15% (mass ratio), and the amount added is calculated based on the amount of calcium hydroxide added according to the reaction equation for generating calcium phosphate.
[0015] Furthermore, the sodium fatty acid in steps (3) and (4) is one or a combination of sodium stearate and sodium palmitate.
[0016] Furthermore, the concentration of the sodium fatty acid solution in step (3) is 10-20% (mass ratio).
[0017] Furthermore, the soluble calcium salt in step (4) is one or a combination of calcium chloride and calcium nitrate.
[0018] Furthermore, the concentration of the soluble calcium salt in step (4) is 5-15% (mass ratio), and the amount added is calculated based on the amount of sodium fatty acid added according to the reaction equation for generating calcium fatty acid.
[0019] Furthermore, the drying temperature in step (5) is 100-130°C.
[0020] Compared with the prior art, the emergence of the present invention marks a major innovation in the field of nano calcium carbonate material processing. Its unique advantages and significant beneficial effects are specifically reflected in the following aspects, which profoundly reflect the depth and breadth of technological progress:
[0021] 1. Innovative coating strategy to effectively inhibit the aggregation of calcium carbonate powder: When processing nano-calcium carbonate, traditional methods often face the problem of spontaneous aggregation and agglomeration of powders due to high specific surface area and surface energy, which seriously affects its application performance. The present invention takes a unique approach and uses the chemical reaction of calcium hydroxide and phosphoric acid to cleverly coat the surface of nano-calcium carbonate with a layer of calcium phosphate. This dense coating layer not only serves as a physical barrier to effectively isolate the direct contact between nanoparticles and prevent them from agglomerating due to mutual attraction, but also enhances the stability of the particles through chemical bonding, significantly slowing down the soft agglomeration phenomenon unique to nano-calcium carbonate. This innovative strategy fundamentally solves the problems that have long plagued the industry and lays a solid foundation for the widespread application of nano-calcium carbonate.
[0022] 2. Optimize the coating process to achieve uniform coverage of sodium fatty acids: To address the problem of poor dispersibility caused by uneven coating of sodium fatty acids, the present invention innovatively introduces the "low concentration + high temperature treatment + cooling coating" technology. This technology carefully controls the reaction conditions, first using a low concentration to ensure that the sodium fatty acid molecules can fully penetrate into the surface of nano-calcium carbonate, and then uses high temperature to promote rapid interactions between molecules to make the coating tighter. The cooling step cleverly utilizes the physical and chemical changes caused by temperature changes to further optimize the uniformity and density of the coating layer. This series of optimization measures greatly increases the repulsive force between calcium carbonate particles, making it easy to open powder agglomerates that were originally difficult to disperse, and achieving a qualitative leap in dispersion performance.
[0023] 3. The double decomposition method introduces fatty acid calcium to break through traditional constraints: In view of the fact that excessive sodium fatty acid may aggravate the aggregation of powders as a binder, the present invention creatively adopts the double decomposition method to replace part of the sodium fatty acid with fatty acid calcium for coating. Fatty acid calcium not only retains the excellent dispersibility of sodium fatty acid, but also effectively avoids the negative effects caused by excessive amount due to its molecular structure characteristics. This substitution strategy not only simplifies the production process and reduces costs, but more importantly, it fundamentally alleviates the aggregation of powders aggravated by excessive binders, further slows down the soft agglomeration of nano calcium carbonate, and improves the overall quality and market competitiveness of the product.
[0024] 4. The three coating technologies work synergistically to achieve a comprehensive upgrade in performance: The core of the present invention is to organically integrate the above three coating technologies to form a unique synergistic mechanism. This synergy is not only reflected in the superposition of the effects of a single technology, but also in the comprehensive effect of mutual promotion and mutual enhancement between them. Through the chemical barrier effect of calcium phosphate, the uniform coating of sodium fatty acid, and the substitution optimization of calcium fatty acid, the present invention successfully overcomes the stubborn problem of poor dispersibility of nano-calcium carbonate due to soft agglomeration, and achieves a comprehensive upgrade of material performance. This technological breakthrough not only opens up a new path for the deep processing and wide application of nano-calcium carbonate, but also provides valuable reference and reference for technological innovation in related fields. DETAILED DESCRIPTION
[0025] The present invention will be further described in detail below in conjunction with specific embodiments. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application.
[0026] In an embodiment of the present invention, a surface treatment method for improving the dispersibility of nano calcium carbonate comprises the following steps:
[0027] (1) selecting high-quality limestone and calcining it at high temperature to obtain raw lime, then digesting the raw lime with tap water to obtain lime milk, and then subjecting the lime milk to carbonation reaction with carbon dioxide in a carbonation tower, and obtaining a nano calcium carbonate suspension after the reaction is completed;
[0028] (2) transferring the calcium carbonate suspension of step (1) into a treatment tank with heat preservation and cooling functions, heating the suspension to 85-100° C., then adding a suspension containing 2.0-5.0% calcium hydroxide (calcium carbonate dry basis weight), starting stirring, and then adding a corresponding amount of phosphoric acid solution to the suspension at a regular interval of 10-30 minutes. When the phosphoric acid solution is added, a 1# calcium carbonate suspension can be obtained;
[0029] (3) maintaining the temperature of the 1# calcium carbonate suspension at 85-100° C., adding a solution containing 0.5-1.5% sodium fatty acid (calcium carbonate dry basis weight), and then slowly cooling while stirring for surface treatment, the cooling time being 30-60 min, and when the temperature drops to 30° C., a 2# calcium carbonate suspension can be obtained;
[0030] (4) reheating the 2# calcium carbonate suspension to 65-80° C., adding a solution containing 2.5-3.5% fatty acid sodium (calcium carbonate dry basis weight), starting stirring, and then continuing to add a corresponding amount of soluble calcium salt solution to the suspension at regular intervals of 10-20 min to coat the fatty acid calcium;
[0031] (5) Dehydrating the calcium carbonate slurry through a filter press, drying, and crushing to obtain nano calcium carbonate finished powder.
[0032] The concentration of the phosphoric acid solution in step (2) is 5-15% (mass ratio), and the amount added is calculated based on the amount of calcium hydroxide added according to the reaction equation for generating calcium phosphate;
[0033] The fatty acid sodium in steps (3) and (4) is one or a combination of sodium stearate and sodium palmitate;
[0034] The concentration of the sodium fatty acid solution in step (3) is 10-20% (mass ratio);
[0035] The soluble calcium salt in step (4) is one or a combination of calcium chloride and calcium nitrate;
[0036] The concentration of the soluble calcium salt in step (4) is 5-15% (mass ratio), and the amount added is calculated based on the amount of sodium fatty acid added according to the reaction equation for generating calcium fatty acid.
[0037] The drying temperature in step (5) is 100-130°C.
[0038] Technical principle of the present invention:
[0039] When deeply discussing the innovative surface treatment method for improving the dispersibility of nano-calcium carbonate of the present invention, we should not only elaborate on the specific operations in each step, but also deeply analyze the specific role of each raw material, the synergistic mechanism between them and the importance of process parameter optimization, so as to fully demonstrate how this technology can achieve unexpected results, which is specifically reflected in the following aspects:
[0040] (I) Specific role and synergistic mechanism of raw materials
[0041] 1. Raw material selection and initial preparation
[0042] 1) High-quality limestone: As the starting material, its purity and crystal structure directly affect the quality of the final product. Raw lime is produced by high-temperature calcination. This process effectively removes impurities and provides a high-purity calcium source for subsequent reactions.
[0043] 2) Carbonation reaction: Through the carbonation reaction of lime milk and carbon dioxide, the reaction conditions such as temperature, pressure and carbon dioxide flow rate are precisely controlled to generate a nano calcium carbonate suspension with uniform particle size and good dispersion. In this step, carbon dioxide is the key carbon source, and the precise control of its concentration and flow rate is crucial for the formation of nanoparticles.
[0044] 2. Phosphoric acid treatment stage
[0045] 1) Phosphoric acid solution: Add phosphoric acid solution to react with calcium hydroxide to form calcium phosphate. This process not only helps to adjust the pH value of the suspension, but more importantly, forms a calcium phosphate protective layer on the surface of the nano calcium carbonate particles, effectively preventing agglomeration between particles and significantly improving dispersibility. The concentration of the phosphoric acid solution needs to be precisely controlled to ensure that the reaction is complete and not excessive, so as to avoid adverse effects on subsequent steps.
[0046] 2) Synergistic effect: The formation of the calcium phosphate layer is closely related to the amount of calcium hydroxide added. The two build a stable protective layer on the surface of the nanoparticles through chemical reaction, laying a good foundation for subsequent surface treatment.
[0047] 3. Surface treatment of sodium fatty acid
[0048] 1) Sodium stearate and sodium palmitate: These two sodium fatty acids, as surfactants, can further improve the dispersibility and wettability of nano calcium carbonate. They form a hydrophobic layer by adsorbing on the surface of particles, effectively preventing direct contact between particles and thus preventing agglomeration. At the same time, the selective use of sodium fatty acids (alone or in combination) can be adjusted according to specific application requirements to achieve the best effect.
[0049] 2) Synergistic effect: After adding a lower concentration of sodium fatty acid for the first time, the temperature is slowly lowered, so the sodium fatty acid molecules have enough time to evenly cover the surface of the particles. Subsequently, a higher concentration of sodium fatty acid is added again at a higher temperature, and the fatty acid calcium is coated with a soluble calcium salt (such as calcium chloride and calcium nitrate). This double treatment significantly enhances the hydrophobicity and stability of the particle surface, achieving a leap in dispersibility.
[0050] (II) Importance and necessity of process parameter optimization
[0051] 1. Temperature control: The temperature setting in each step is based on the principle of chemical reaction kinetics to ensure that the reaction rate is moderate and the product quality is stable. Too high or too low temperature may affect the reaction efficiency or product performance.
[0052] 2. Time control: Both the addition time of phosphoric acid solution and the cooling time need to be precisely controlled to ensure that the reaction proceeds fully and does not affect the subsequent steps.
[0053] 3. Concentration and addition amount: The concentration and addition amount of each raw material must be added according to the requirements of the chemical reaction. Excess or insufficient amount may lead to reduced product quality or increased cost.
[0054] In summary, the surface treatment method for improving the dispersibility of nano-calcium carbonate of the present invention not only significantly improves the dispersibility and stability of nano-calcium carbonate, but also achieves comprehensive optimization of product performance through carefully designed raw material selection and ratio, strict process parameter control and multi-step coordinated treatment. The fine control of each step and the synergy between the raw materials have jointly contributed to this unexpected technical effect, highlighting the key role of process optimization in the preparation of nanomaterials.
[0055] In order to make the disclosure of the present invention more complete, it is described below through more specific embodiments.
[0056] Example 1
[0057] A surface treatment method for improving the dispersibility of nano calcium carbonate comprises the following steps:
[0058] (1) high-quality limestone is subjected to high temperature to obtain raw lime, lime is digested with tap water to obtain lime milk, the solid content of the lime milk is adjusted to 10%, the lime milk is transferred to a carbonation tower, cooled to 23° C., 0.2% sucrose is added, and carbon dioxide gas is introduced to carry out carbonation reaction. When the conductivity of the slurry drops to the minimum value, the reaction is stopped to obtain a nano calcium carbonate suspension;
[0059] (2) the calcium carbonate suspension of step (1) is transferred into a treatment tank with heat preservation and cooling functions, the suspension is heated to 100° C., then a suspension containing 5.0% calcium hydroxide (calcium carbonate dry basis weight) is added, stirring is started, and then a solution containing 4.4% phosphoric acid (calcium carbonate dry basis weight) (concentration 5%) is added to the suspension in equal amounts for 10 min at a time, and when the phosphoric acid solution is added, a calcium carbonate suspension #1 is obtained;
[0060] (3) maintaining the temperature of the 1# calcium carbonate suspension at 100° C., adding a solution (concentration 10%) containing 1.5% sodium stearate (calcium carbonate dry basis weight), and then slowly cooling the mixture while stirring for surface treatment. The cooling time is 60 min. When the temperature drops to 30° C., a 2# calcium carbonate suspension can be obtained;
[0061] (4) The 2# calcium carbonate suspension was reheated to 65° C., and a solution containing 2.5% sodium stearate (on a dry basis of calcium carbonate) (concentration 10%) was added, stirring was started, and then a solution containing 0.45% calcium chloride (on a dry basis of calcium carbonate) (concentration 15%) was added to the suspension in equal amounts for 20 min at a time for secondary surface treatment;
[0062] (5) The slurry is dehydrated by a plate and frame filter press, and the pressed material is dried at 120° C. and finally crushed to obtain nano calcium carbonate powder.
[0063] Example 2
[0064] A surface treatment method for improving the dispersibility of nano calcium carbonate comprises the following steps:
[0065] (1) high-quality limestone is subjected to high temperature to obtain raw lime, lime is digested with tap water to obtain lime milk, the solid content of the lime milk is adjusted to 10%, the lime milk is transferred to a carbonation tower, cooled to 23° C., 0.2% sucrose is added, and carbon dioxide gas is introduced to carry out carbonation reaction. When the conductivity of the slurry drops to the minimum value, the reaction is stopped to obtain a nano calcium carbonate suspension;
[0066] (2) the calcium carbonate suspension of step (1) is transferred into a treatment tank with heat preservation and cooling functions, the suspension is heated to 85° C., then a suspension containing 2.0% calcium hydroxide (calcium carbonate dry basis weight) is added, stirring is started, and then a solution containing 1.8% phosphoric acid (calcium carbonate dry basis weight) (concentration 15%) is added to the suspension in equal amounts for 30 minutes at a time, and when the phosphoric acid solution is added, a calcium carbonate suspension #1 is obtained;
[0067] (3) maintaining the temperature of the 1# calcium carbonate suspension at 85° C., adding a solution (concentration 20%) containing 0.5% sodium palmitate (calcium carbonate dry basis weight), and then slowly cooling the mixture while stirring for surface treatment. The cooling time is 30 min. When the temperature drops to 30° C., a 2# calcium carbonate suspension can be obtained;
[0068] (4) reheating the 2# calcium carbonate suspension to 80° C., adding a solution (concentration 20%) containing 3.5% sodium palmitate (calcium carbonate dry basis weight), starting stirring, and then adding an equal amount of a solution (concentration 5%) containing 1.03% calcium nitrate (calcium carbonate dry basis weight) to the suspension for 20 min at a time for secondary surface treatment;
[0069] (5) The slurry is dehydrated by a plate and frame filter press, and the pressed material is dried at 120° C. and finally crushed to obtain nano calcium carbonate powder.
[0070] Example 3
[0071] A surface treatment method for improving the dispersibility of nano calcium carbonate comprises the following steps:
[0072] (1) high-quality limestone is subjected to high temperature to obtain raw lime, lime is digested with tap water to obtain lime milk, the solid content of the lime milk is adjusted to 10%, the lime milk is transferred to a carbonation tower, cooled to 23° C., 0.2% sucrose is added, and carbon dioxide gas is introduced to carry out carbonation reaction. When the conductivity of the slurry drops to the minimum value, the reaction is stopped to obtain a nano calcium carbonate suspension;
[0073] (2) the calcium carbonate suspension of step (1) is transferred into a treatment tank with heat preservation and cooling functions, the suspension is heated to 92° C., then a suspension containing 3.5% calcium hydroxide (calcium carbonate dry basis weight) is added, stirring is started, and then a solution containing 3.1% phosphoric acid (calcium carbonate dry basis weight) (concentration 10%) is added to the suspension in equal amounts for 20 min at a time, and when the phosphoric acid solution is added, a calcium carbonate suspension #1 is obtained;
[0074] (3) maintaining the temperature of the 1# calcium carbonate suspension at 92° C., adding a solution (concentration 15%) containing 1.0% sodium stearate / sodium palmitate=1 / 1 (calcium carbonate dry basis weight), and then slowly cooling the mixture while stirring for surface treatment. The cooling time is 45 min. When the temperature drops to 30° C., a 2# calcium carbonate suspension can be obtained;
[0075] (4) The 2# calcium carbonate suspension was reheated to 72° C., and a solution (concentration 15%) containing 3.0% sodium stearate / sodium palmitate = 1 / 1 (calcium carbonate dry basis weight) was added, stirring was started, and then a solution (concentration 10%) containing 0.57% calcium chloride (calcium carbonate dry basis weight) was added to the suspension in equal amounts for 15 min to perform secondary surface treatment;
[0076] (5) The slurry is dehydrated by a plate and frame filter press, and the pressed material is dried at 120° C. and finally crushed to obtain nano calcium carbonate powder.
[0077] Example 4
[0078] A surface treatment method for improving the dispersibility of nano calcium carbonate comprises the following steps:
[0079] (1) high-quality limestone is subjected to high temperature to obtain raw lime, lime is digested with tap water to obtain lime milk, the solid content of the lime milk is adjusted to 10%, the lime milk is transferred to a carbonation tower, cooled to 23° C., 0.2% sucrose is added, and carbon dioxide gas is introduced to carry out carbonation reaction. When the conductivity of the slurry drops to the minimum value, the reaction is stopped to obtain a nano calcium carbonate suspension;
[0080] (2) the calcium carbonate suspension of step (1) is transferred into a treatment tank with heat preservation and cooling functions, the suspension is heated to 95° C., then a suspension containing 3.5% calcium hydroxide (calcium carbonate dry basis weight) is added, stirring is started, and then a solution containing 3.1% phosphoric acid (calcium carbonate dry basis weight) (concentration 10%) is added to the suspension in equal amounts for 20 minutes at a time, and when the phosphoric acid solution is added, a calcium carbonate suspension #1 is obtained;
[0081] (3) maintaining the temperature of the 1# calcium carbonate suspension at 95° C., adding a solution (concentration 15%) containing 1.0% sodium stearate (calcium carbonate dry basis weight), and then slowly cooling the mixture while stirring for surface treatment. The cooling time is 45 min. When the temperature drops to 30° C., a 2# calcium carbonate suspension can be obtained;
[0082] (4) The 2# calcium carbonate suspension was reheated to 75° C., and a solution (concentration 15%) containing 3.0% sodium stearate (calcium carbonate dry basis weight) was added, stirring was started, and then a solution (concentration 10%) containing 0.27% calcium chloride and 0.40% calcium nitrate (calcium carbonate dry basis weight) was added to the suspension in equal amounts for 15 min for secondary surface treatment;
[0083] (5) The slurry is dehydrated by a plate and frame filter press, and the pressed material is dried at 120° C. and finally crushed to obtain nano calcium carbonate powder.
[0084] Comparative Example 1
[0085] A method for preparing nano calcium carbonate powder comprises the following steps:
[0086] (1) high-quality limestone is subjected to high temperature to obtain raw lime, lime is digested with tap water to obtain lime milk, the solid content of the lime milk is adjusted to 10%, the lime milk is transferred to a carbonation tower, cooled to 23° C., 0.2% sucrose is added, and carbon dioxide gas is introduced to carry out carbonation reaction. When the conductivity of the slurry drops to the minimum value, the reaction is stopped to obtain a nano calcium carbonate suspension;
[0087] (2) moving the calcium carbonate suspension of step (1) into a treatment tank, heating the suspension to 65° C., and then adding a solution containing 4.0% sodium stearate (calcium carbonate dry basis weight) for surface treatment;
[0088] (3) The slurry is dehydrated by a plate and frame filter press, and the pressed material is dried at 120° C. and finally crushed to obtain nano calcium carbonate powder.
[0089] Comparative Example 2
[0090] A method for preparing nano calcium carbonate powder comprises the following steps:
[0091] (1) high-quality limestone is subjected to high temperature to obtain raw lime, lime is digested with tap water to obtain lime milk, the solid content of the lime milk is adjusted to 10%, the lime milk is transferred to a carbonation tower, cooled to 23° C., 0.2% sucrose is added, and carbon dioxide gas is introduced to carry out carbonation reaction. When the conductivity of the slurry drops to the minimum value, the reaction is stopped to obtain a nano calcium carbonate suspension;
[0092] (2) the calcium carbonate suspension of step (1) is transferred into a treatment tank with heat preservation and cooling functions, the suspension is heated to 100° C., then a suspension containing 5.0% calcium hydroxide (calcium carbonate dry basis weight) is added, stirring is started, and then a solution containing 4.4% phosphoric acid (calcium carbonate dry basis weight) (concentration 5%) is added to the suspension in equal amounts for 10 min at a time, and when the phosphoric acid solution is added, a calcium carbonate suspension #1 is obtained;
[0093] (3) The 1# calcium carbonate suspension was cooled to 65° C., and then a solution containing 4.0% sodium stearate (calcium carbonate dry basis weight) was added for surface treatment;
[0094] (4) The slurry is dehydrated by a plate and frame filter press, and the pressed material is dried at 120° C. and finally pulverized to obtain nano calcium carbonate powder.
[0095] Comparative Example 3
[0096] A method for preparing nano calcium carbonate powder comprises the following steps:
[0097] (1) high-quality limestone is subjected to high temperature to obtain raw lime, lime is digested with tap water to obtain lime milk, the solid content of the lime milk is adjusted to 10%, the lime milk is transferred to a carbonation tower, cooled to 23° C., 0.2% sucrose is added, and carbon dioxide gas is introduced to carry out carbonation reaction. When the conductivity of the slurry drops to the minimum value, the reaction is stopped to obtain a nano calcium carbonate suspension;
[0098] (2) the calcium carbonate suspension of step (1) is transferred into a treatment tank with heat preservation and cooling functions, the suspension is heated to 100° C., then a suspension containing 5.0% calcium hydroxide (calcium carbonate dry basis weight) is added, stirring is started, and then a solution containing 4.4% phosphoric acid (calcium carbonate dry basis weight) (concentration 5%) is added to the suspension in equal amounts for 10 min at a time, and when the phosphoric acid solution is added, a calcium carbonate suspension #1 is obtained;
[0099] (3) cooling the 1# calcium carbonate suspension to 65° C., and then adding a solution containing 1.5% sodium stearate (calcium carbonate dry basis weight) for surface treatment to obtain a 2# calcium carbonate suspension;
[0100] (4) maintaining the temperature of the 2# calcium carbonate suspension at 65° C., adding a solution (concentration 10%) containing 2.5% sodium stearate (calcium carbonate dry basis weight), starting stirring, and then adding an equal amount of a solution (concentration 15%) containing 0.45% calcium chloride (calcium carbonate dry basis weight) to the suspension for 20 min for secondary surface treatment;
[0101] (5) The slurry is dehydrated by a plate and frame filter press, and the pressed material is dried at 120° C. and finally crushed to obtain nano calcium carbonate powder.
[0102] Dispersion test:
[0103] In order to simulate the soft agglomeration formed by the powder after packaging or storage extrusion, the present invention uniformly uses an electronic universal testing machine to extrude the powder at a pressure of 1.0 MPa. The nano calcium carbonate powder of the embodiment and the comparative example is divided into two parts, one part is extruded at a pressure of 1.0 MPa, and the other part is not extruded. Then, according to the formula of 107 glue (20000 mPa.s) / powder = 55 / 45, a gravity mixer is used to prepare a base glue, and then a butterfly sample is prepared with the base glue. Finally, the macroscopic dispersion of the powder is judged according to the number of particles visible on the butterfly sample. The test results are shown in Table 1.
[0104] Table 1 Dispersion test results
[0105]
[0106] When we analyze the test results presented in Table 1, we can easily find that the surface treatment method of the present invention shows remarkable technical advantages compared with the traditional comparative example 1, especially in solving the long-standing technical problem of poor macroscopic dispersion of materials caused by soft agglomeration. Although traditional surface treatment methods can play a certain role under certain conditions, their limitations are fully revealed when facing complex and changeable material systems, and it is difficult to effectively curb the negative impact of soft agglomeration on dispersion performance.
[0107] Further comparing Comparative Example 1 with Comparative Example 2, we can clearly see that after the introduction of the calcium phosphate coating strategy, the macroscopic dispersion of the material has been significantly improved. As a material with good biocompatibility and stable chemical properties, calcium phosphate has unique surface chemical properties that can effectively reduce the interaction force between particles, thereby breaking the original soft agglomeration structure and promoting the uniform distribution of particles in the medium. This discovery not only broadens the application scope of calcium phosphate in the field of materials science, but also provides us with a new idea to optimize the dispersion performance of materials.
[0108] By carefully comparing Comparative Example 2 with Comparative Example 3, we found that fatty acid calcium coating also showed excellent ability to improve macroscopic dispersibility. With its good lubricity and interfacial activity, fatty acid calcium can form a uniform coating layer on the surface of particles, effectively preventing direct contact and agglomeration between particles, thereby improving the dispersion effect of the material. This discovery not only verifies the potential of fatty acid calcium as a surface modifier, but also reveals that the dispersion performance of the material can be further optimized by adjusting the type of coating material.
[0109] It is worth mentioning that when we compare Example 1 with Comparative Example 3, the comprehensive application effect of low concentration + high temperature treatment + cooling coating technology is particularly prominent. This innovative surface treatment technology achieves fine control of the surface properties of the material by precisely controlling the treatment conditions, such as using a low concentration solution to reduce the adverse effects on the material body, combining high temperature treatment to promote the uniform formation of the coating layer, and achieving the solidification of the coating layer during the cooling process. This technology not only significantly improves the macroscopic dispersibility of the material, but also retains the original excellent performance of the material, showing extremely high technical value and application prospects.
[0110] In summary, the surface treatment method of the present invention has made significant progress in solving the problem of poor macroscopic dispersion of materials. It not only breaks through the limitations of traditional surface treatment methods, but also achieves comprehensive optimization of material surface properties by introducing calcium phosphate and fatty acid calcium coating strategies and innovative low concentration + high temperature treatment + cooling coating technology. These technological advances have not only brought new solutions to the field of materials science, but also injected new vitality into the development of related industries.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A surface treatment method for improving the dispersibility of nano calcium carbonate, characterized in that, The following steps are involved: (1) limestone is calcined to obtain raw lime, and then the raw lime is digested with water to obtain lime milk, and then the lime milk is subjected to carbonation reaction with carbon dioxide in a carbonating tower, and the reaction is terminated to obtain a nano calcium carbonate suspension; (2) moving the nano calcium carbonate suspension of step (1) into a treatment tank, heating the suspension to 85-100° C., then adding a suspension containing calcium hydroxide, starting stirring, and then adding a corresponding amount of phosphoric acid solution to the suspension at regular intervals of 10-30 min. After the phosphoric acid solution is added, a 1# calcium carbonate suspension can be obtained; (3) maintaining the temperature of the 1# calcium carbonate suspension at 85-100° C., adding a solution containing sodium fatty acid, and then cooling the mixture while stirring for surface treatment for 30-60 min. When the temperature drops below 30° C., a 2# calcium carbonate suspension can be obtained; (4) reheating the 2# calcium carbonate suspension to 65-80° C., adding a solution containing sodium fatty acid, starting stirring, and then continuing to add a corresponding amount of soluble calcium salt solution to the suspension at regular intervals of 10-20 min to coat the calcium fatty acid; (5) Dehydrating the calcium carbonate slurry through a filter press, drying, and crushing to obtain nano calcium carbonate finished powder.
2. The surface treatment method according to claim 1, wherein the nano-calcium carbonate dispersion is In step (2), a suspension containing 2.0-5.0% calcium hydroxide is added.
3. The surface treatment method according to claim 1 which improves the dispersibility of nano-calcium carbonate, is characterized in that: The mass concentration of the phosphoric acid solution in step (2) is 5-15%, and the added amount is calculated based on the added amount of calcium hydroxide according to the reaction equation for generating calcium phosphate.
4. The surface treatment method according to claim 1, wherein the nano-calcium carbonate dispersion is In step (3), a solution containing 0.5-1.5% sodium fatty acid is added.
5. The surface treatment method for improving the dispersibility of nano calcium carbonate according to claim 1, wherein The fatty acid sodium in step (3) and step (4) is one or a combination of sodium stearate and sodium palmitate.
6. The surface treatment method according to claim 1, 4 or 5, wherein the nano-calcium carbonate dispersion is The mass concentration of the sodium fatty acid solution is 10-20%.
7. The surface treatment method for improving the dispersibility of nano calcium carbonate according to claim 1, characterized in that, In step (4), a solution containing 2.5-3.5% sodium fatty acid is added.
8. The surface treatment method for improving the dispersibility of nano calcium carbonate according to claim 1, characterized in that, The soluble calcium salt in step (4) is one or a combination of calcium chloride and calcium nitrate.
9. The surface treatment method for improving the dispersibility of nano calcium carbonate according to claim 1, characterized in that, The mass concentration of the soluble calcium salt in step (4) is 5-15%, and the amount added is calculated based on the amount of sodium fatty acid added according to the reaction equation for generating calcium fatty acid.
10. The surface treatment method for improving the dispersibility of nano calcium carbonate according to claim 1, characterized in that, The drying temperature in step (5) is 100-130°C.